Antigonon Leptopus Extract as a Renewable Energy Source Material for the Development of Dye-Sensitized Solar Cells (DSSC) - Darmawan, Muhammad Iman; Mandala Putra, Hadian; Ali Majdi, Yogi Stiamil; Gunawan, Istajir Adi (Lembaga Bale Literasi, 2025)
Solar cells are devices composed of solar panels that convert light into electrical energy. Conventionally, energy is primarily derived from fossil fuels, which are non-renewable resources. Consequently, many researchers have sought alternative sources of energy. One such innovation is the Dye-Sensitized Solar Cell (DSSC). This study aims to investigate the effect of Antigonon leptopus flower dye as an active material in Dye-Sensitized Solar Cells (DSSC). The absorbance testing was conducted using a UV-Visible Spectrophotometer (1601 PC), while current and voltage (I–V) measurements were carried out using a Keithley instrument. The results showed that the natural dye extracted from the leaves of Antigonon leptopus exhibited an absorbance spectrum in the range of 200–800 nm. These findings suggest that Antigonon leptopus has potential as a natural sensitizer material for application in Dye-Sensitized Solar Cells (DSSC).